Factors relevant to work participation from the perspective of adults with developmental dyslexia: a systematic review of qualitative studies - Joost de Beer; Yvonne Heerkens; Josephine Engels; Jac van der Klink (BMC, 2022)
Abstract Background This review is focused on workers with developmental dyslexia (DD). In this review DD is considered an expression of neurodiversity, a consequence of a natural variant of the brain. Evidence was synthesized to explore which factors workers with DD consider relevant for their participation in work and whether these factors reflect shifts in the concepts of health and sustainable employability. The factors were classified according to the International Classification of Functioning, Disability and Health (ICF), adapted for occupational health. Methods A systematic review of qualitative studies was performed. Two search strings were used to determine the population and the context of work. The factors were classified using a recently proposed rearrangement of the ICF scheme that places participation in a central position and incorporates preliminary lists of work-related environmental factors and personal factors. Results Fifty-one factors were found that appeared in 35% or more of the included studies and that were relevant to work participation according to the workers themselves. These factors were dispersed over all ICF categories. In the category Functions and Structures (11 factors), most of the factors had negative connotations. In the category Activities (9 factors), all the factors cause difficulties, except speaking (which is ambiguous). In the category Participation (4 factors), the formal relationships are important for the degree of participation. Overall, more than half of the factors are environmental (18) or personal (9) and they both hinder and facilitate work participation. Conclusions The results of this review give an indication for the importance of the biopsychosocial model as a relevant approach for people with a disability in the world of work. This review also adds data for the usefulness of the proposals for the reconsideration of the ICF scheme. The data has not (yet) returned any visible trends revealing that the concept of neurodiversity is common in organizations.